The microneme proteins EtMIC4 and EtMIC5 of Eimeria tenella form a novel, ultra-high molecular mass protein complex that binds target host cells. - Periz, J; Gill, A; Hunt, L; Brown, P; Tomley, F (2007)
Eimeria tenella, in common with other parasitic protozoa of the phylum Apicomplexa, invades host cells using an actinomyosin-powered "glideosome" complex and requires the secretion of adhesive proteins from the microneme organelles onto the parasite surface. Microneme proteins of E. tenella include EtMIC4, a transmembrane protein that has multiple thrombospondin type I domains and calcium-binding epidermal growth factor-like domains in its extracellular domain, and EtMIC5, a soluble protein composed of 11 tandemly repeated domains that belong to the plasminogen-apple-nematode superfamily. We show here that EtMIC4 and EtMIC5 interact to form an oligomeric, ultrahigh molecular mass protein complex. The complex was purified from lysed parasites by non-denaturing techniques, and the stoichiometry was shown to be [EtMIC4](2):[EtMIC5](1), with an octamer of EtMIC4 bound non-covalently to a tetramer of EtMIC5. The complex is formed within the parasite secretory pathway and is maintained after secretion onto the surface of the parasite. The purified complex binds to a number of epithelial cell lines in culture. Identification and characterization of this complex contributes to an overall understanding of the role of multimolecular protein complexes in specific interactions between pathogens and their hosts during infection.